Primary productivity in a minor estuary along the south west coast of India - Prema, P; Palavesam, P; Venkadesh, B (Indian Journal of Fisheries, 2011)
The study deals with the primary production, as measured in four different sampling stations (S1 to S4), of a minor estuary (Rajakkamangalam) in Kanyakumari district, south west coast of India. The results indicated that, the maximum GPP value of 2.313 gCm2 -1day -1 was recorded at S4 against theminimum (0.714 gCm2 -1day -1) in S3 during 1997. In 1998, the highest GPP of 2.841 gCm2 -1day -1 was found in S1 followed by S4. The highest NPP value of 1.109 gCm2 -1day -1was noticed at S4 against the lowest value of 0.813 gCm2 -1day -1 of at S3. The seasonal variations were quite distinct and showed high values during south west monsoon against the low values during north east monsoon. Duncan’s multiple range test showed significant variations (P